Development home automation and safety circuit breaker with ESP8266 microcontroller - Noor Azhuan, Nur Azura; Samsudin, Adam; James, Brandon; Hussin, Nor Hafizah; Mohd Said, Rahaini; Hairol Anuar, Siti Haryanti; Saidin, Norshaza Atika; Abd Aziz, Mohd Syafiq (Semarak Ilmu Publishing, 2024)
This study addresses common challenges in conventional home electricity usage, with a focus on safety concerns related to gas leakage. In many cases, current technology lacks immediate power usage tracking, and manual control of circuit breakers, sockets, and lamps proves challenging, especially when users are away. To overcome these issues, this project employs an ESP8266 Wi-Fi Shield Arduino as a microcontroller connected to sensors and a servo motor. In the proposed system, users can detect gas leakage, control lamp and socket activation, and manage the Residual Current Circuit Breaker (RCCB) with the servo motor by utilizing Blynk apps for monitoring. The main objective of this study is to design a centralized system that enables users to control and manage home electrical appliances via smartphone. The methodology involves developing a microcontroller program for the Cytron ESP8266 WiFi Shield, creating an auto-reclosure circuit breaker notification, and building a practical gas leakage detection prototype for household applications. Additionally, the system addresses lightning-induced overvoltage issues, analyzes nuisance tripping, and provides control over home appliance usage while effectively detecting hazardous gas leaks. The approach is based on Blynk and the ESP8266 Wi-Fi Shield Arduino by incorporating data from limit switch conditions, relay status, voltage sensors, current sensors, and power consumption. The results justify the servo's efficient performance, reliable relay operations, and precise gas sensor triggering. Despite slight variations in current and voltage values compared to the actual meter, the system offers a successful and systematic approach to enhancing home electricity management and safety.